Short and Medium Term Neurological Outcomes of Children with Antenatal or Neonatal Exposure to Severe Acute Respiratory Syndrome Coronavirus 2 - Fatih Mehmet Akif Özdemir; Fatma Hilal Yılmaz (Galenos Publishing House, 2023)
Objective: Neurological complications are among the main causes of mortality and morbidity in antenatal infections. Data on the long-term outcomes of infants exposed to severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection in the antenatal or neonatal period are limited. This study aimed to investigate potential neurological complications in children with antenatal or neonatal exposure to SARS-CoV-2. Method: In this prospective cross-sectional study, infants and toddlers with a history of antenatal or neonatal SARS-CoV-2 exposure underwent neurological evaluation by a pediatric neurologist. Results: Of 31 children (19 males, median age 9.3 months) included in the study, maternal coronavirus disease-2019 (COVID-19) diagnosis was made in the first trimester of pregnancy in 1, the second trimester in 3, and the third trimester in 25 children. Two children were diagnosed with COVID-19 in the neonatal period, and 3 children with maternal COVID-19 diagnosis during pregnancy were also diagnosed with COVID-19 neonatally. On neurological examination, hypotonia and motor/social delays were observed in 1, microcephaly in 2, and macrocephaly in 1 child. Of the 8 children evaluated with magnetic resonance imaging, 1 had findings consistent with Joubert syndrome and the others were normal. All infants passed the standard auditory brainstem response test. The only ocular abnormalities detected were retinopathy of prematurity (stage 3) in 1 infant and poor eye contact and object tracking in the child with Joubert syndrome. Conclusion: Our study suggests that neurological development is mostly favorable in infants and toddlers exposed to SARS-CoV-2 in the antenatal or neonatal period.